2007
DOI: 10.1093/rheumatology/kel159
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of IL-23p19 expression in rheumatoid arthritis synovial fibroblasts by IL-17 through PI3-kinase-, NF- B- and p38 MAPK-dependent signalling pathways

Abstract: IL-23p19 is over-expressed in RA synovial fibroblasts and IL-17 appears to up-regulate the expression of IL-23p19 in RA synovial fibroblasts via PI3-kinase/Akt, NF-kappaB- and p38-MAPK-mediated pathways. These results suggest that a disruption of interaction between IL-17 and IL-23p19 may provide a new therapeutic approach in the treatment of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
131
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(140 citation statements)
references
References 34 publications
8
131
1
Order By: Relevance
“…Furthermore, IL-17-producing ␥/␦ T cells were induced equivalently in response to stimulation by IFA plus solution in the absence of type II collagen. Together with results from the previous study demonstrating that IL-17-producing ␥/␦ T cells are induced equally by CFA plus type II collagen and CFA (16), the present data suggest that IL-17-producing ␥/␦ T cells do not recognize the specific antigen (type II collagen) but rather proliferate in response to IL-23, which may be produced locally by synovial cells (44). The ligands of ␥/␦ T cells are largely unknown, and further analysis of possible antigens of IL-17-producing ␥/␦ T cells in CIA could be difficult (47).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Furthermore, IL-17-producing ␥/␦ T cells were induced equivalently in response to stimulation by IFA plus solution in the absence of type II collagen. Together with results from the previous study demonstrating that IL-17-producing ␥/␦ T cells are induced equally by CFA plus type II collagen and CFA (16), the present data suggest that IL-17-producing ␥/␦ T cells do not recognize the specific antigen (type II collagen) but rather proliferate in response to IL-23, which may be produced locally by synovial cells (44). The ligands of ␥/␦ T cells are largely unknown, and further analysis of possible antigens of IL-17-producing ␥/␦ T cells in CIA could be difficult (47).…”
Section: Discussionsupporting
confidence: 80%
“…Here, it was demonstrated that the combination of IL-23 and IL-1␤ synergistically stimulated IL-17 production, but stimulation via ␥/␦ TCR had a limited effect. Given the enhanced expression of IL-1␤ and IL-23 in the inflamed joints of mice with CIA (44,45), these findings suggest that IL-17 production by ␥/␦ T cells in CIA might mainly be an inflammatory cytokine-driven process rather than a TCR signal-driven process.…”
Section: Discussionmentioning
confidence: 86%
“…Research is also ongoing on small molecules that are able to control the intracellular signaling pathways to interfere specifically with IL-17-induced cell activation or, less specifically, act on TNF and IL-1 pathways. Currently, an IL-17-specific signaling pathway has not been identified in synoviocytes (34). Conversely, suppressor of cytokine signaling 3 is an essential negative regulator of IL-23 signaling, and then of IL-17 production (35).…”
Section: An Increasing Choice Of Targets For Treatmentmentioning
confidence: 99%
“…Kim et al revealed that IL-23p19 is over-expressed in RA synovial fibroblasts and IL-17 appears to up-regulate the expression of IL23p19 in RA synovial fibroblasts. 22 The concentration of IL-23p19 correlated with the concentration of IL-17 in synovial fluid and sera of RA patients. They concluded that upregulated IL-23p19 in synovial fluid might be involved in joint destruction in RA through interplay with IL-17.…”
Section: Discussionmentioning
confidence: 92%